Diocesan Bishops Intervention Towards Priests Being Involved in Partisan Politics: An Indonesian Context - Rikardus Jehaut (Journal of Asian Orientation in Theology, 2020)
This article aims to analyze critically the intervention of a diocesan Bishop towards priests being involved in partisan politics in the light of can. 287 2 Code of Canon Law and various affirmations of the Churchs Magisterium, which remain relevant and actual today, with particular reference to the Indonesian context, taking into account the case of a Catholic priest who ran for office and the involvement of several priests of a certain diocese in partisan politics. The author argues that as the leader of the particular church, the diocesan bishop must protect the unity of the whole Church and as consequently, he is obliged to insist on the implementation of all ecclesiastical laws, including in connection with the prohibition on priests not to engage in partisan politics (can. 287, 2). If an individual or group of priests is found to have violated this provision, the Diocesan Bishop must intervene quickly, precisely and decisively in due time. Such an intervention can be seen as an imperative sine qua non in order to protect the identity of the priest and his mission in the world and respect the political role of the laity. The form of intervention can be a verbal warning, written warning, and some canonical sanctions. It should be noted that within the Indonesian context, the intervention like this must be taken because there can be no justification for the direct involvement of the priest in partisan politics, at least at the moment, and also its destructive effects: create tension and division among the faithful and coulddeteriorate the credibility of priests and Churchs institution.